Competing risks simulation with the survsim R package. Issue 7 (9th August 2017) - Moriña, D.; Navarro, A.
ABSTRACT: The goal of this work is to describe how the last version available of the survsim R package can be used to simulate a cohort in a competing risks context by means of a cause-specific hazards model following the ideas introduced by Beyersmann in 2009, and also allowing for individual heterogeneity through a random effect. An example of its application based on a real cohort will be discussed.